Arterial stiffness and progression of structural brain changes: The SMART-MR study. (3rd February 2015) - Jochemsen, Hadassa M.; Muller, Majon; Bots, Michiel L.; Scheltens, Philip; Vincken, Koen L.; Mali, Willem P.T.M.; van der Graaf, Yolanda; Geerlings, Mirjam I.
Abstract : Objective: To examine the cross-sectional and prospective associations between arterial stiffness and structural brain changes within the Second Manifestations of Arterial Disease–Magnetic Resonance (SMART-MR) study, a prospective cohort study among patients with manifest arterial disease. Methods: Distension measurements of the common carotid arteries and a brain MRI were performed in 526 patients (mean age 59 ± 10 years). After a mean follow-up of 4.1 years (range 3.6–5.8), brain MRI was repeated in 308 patients. Brain segmentation was used to quantify total brain volume, cortical gray matter volume, ventricular volume, and white matter lesion (WML) volume (relative to intracranial volume). Infarcts were rated visually. Results: Cross-sectional multivariable regression analyses showed that 1 SD decrease in carotid distension, indicating increased arterial stiffness, was associated with smaller relative total brain and cortical gray matter volumes (B = −0.24%, 95% confidence interval [CI] −0.44 to −0.04%, and B = −0.47%, 95% CI −0.75 to −0.19%), with larger WML volume (B = 0.09%, 95% CI −0.01 to 0.19%), and with higher risk of having nonlacunar (cortical or large subcortical) brain infarcts (relative risk = 1.44, 95% CI 1.14 to 1.81). However, our prospective findings showed that carotid distension was not significantly associated with progression of brain atrophy, WML volume, or brain infarcts. Conclusion: In this population of patients with manifest arterial disease, stiffening of the carotid arteries was cross-sectionally associated with more brain atrophy, WML volume, and nonlacunar infarcts, but did not lead to changes in brain volumes or infarcts after 4 years.